2020
DOI: 10.1007/s00423-020-01891-2
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 not detected in peritoneal fluid: a case of laparoscopic appendicectomy for acute appendicitis in a COVID-19-infected patient

Abstract: Purpose COVID-19 greatly affected millions and affected the way we practice with heightened posture in the way we treat surgical patients. Surgical consensus guidelines are recommending caution in the use of laparoscopy for the theoretical possibility of viral transmission from aerosolization of tissue and peritoneal fluid during surgery. However, there has yet to be proof of COVID-19 being present in peritoneal fluid, justifying the consensus statements. We aim to assess the presence of COVID-19 in peritoneal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
72
0
6

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(85 citation statements)
references
References 7 publications
7
72
0
6
Order By: Relevance
“…Rather, our case highlights the concurrence of a common surgical emergency and COVID-19. In light of our data and of the recent failure to detect COVID-19 in the peritoneal uid of a COVID-19 patient with acute appendicitis [11], we would consider the risk of infectious aerosol development during laparoscopic appendectomy in COVID-19 patients with mild symptoms to be relatively low. However, this is only one case report which clearly limits generalization and precautions such as appropriate personal protective equipment should be used whenever COVID-19 is suspected in a patient, especially as infection of operating personal might result from other sources such as the respiratory system.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Rather, our case highlights the concurrence of a common surgical emergency and COVID-19. In light of our data and of the recent failure to detect COVID-19 in the peritoneal uid of a COVID-19 patient with acute appendicitis [11], we would consider the risk of infectious aerosol development during laparoscopic appendectomy in COVID-19 patients with mild symptoms to be relatively low. However, this is only one case report which clearly limits generalization and precautions such as appropriate personal protective equipment should be used whenever COVID-19 is suspected in a patient, especially as infection of operating personal might result from other sources such as the respiratory system.…”
Section: Resultsmentioning
confidence: 91%
“…There is limited information regarding COVID-19 and acute appendicitis. While one report demonstrating SARS-CoV-2 in the peritoneal uid of a patient with COVID-19 has been published [10], Ngaserin et al reported recently that they could not detect SARS-CoV-2 in the peritoneal uid of a COVID-19 patient with acute appendicitis [11]. Another case report recently described an appendectomy in a patient with COVID-19 but no investigations regarding the presence of SARS-CoV-2 in the appendix were performed [12].…”
Section: Resultsmentioning
confidence: 99%
“…SARS‐CoV2‐RNA has been isolated in blood and feces, while there are conflicting experiences regarding its presence in peritoneal fluid 5,6 . To the best of our knowledge, this is the first report of bile analysis for the presence of SARS‐CoV‐2.…”
mentioning
confidence: 94%
“…Some reports have identi ed the presence of genetic material in the PF, and it was associated with PD failure (12,13). However, other reports have not detected the presence of the virus in the PF (14)(15)(16)(17).…”
Section: Read Full Licensementioning
confidence: 99%